Question Solve the following system of equations using an inverse matrix. You must also indicate the inverse matrix, \( A^{-1} \), that was used to solve the system. You may optionally write the inverse matrix with a scalar coefficient. \[ \begin{array}{r}-x-6 y=8 \\ -3 x-10 y=6\end{array} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the system of equations using an inverse matrix approach, we first need to express it in the form \(AX = B\). The given equations can be rewritten as: \[ \begin{bmatrix} -1 & -6 \\ -3 & -10 \end{bmatrix} \begin{bmatrix} x \\ y \end{bmatrix} = \begin{bmatrix} 8 \\ 6 \end{bmatrix} \] Here, \(A = \begin{bmatrix} -1 & -6 \\ -3 & -10 \end{bmatrix}\) and \(B = \begin{bmatrix} 8 \\ 6 \end{bmatrix}\). Now, let's find the inverse of matrix \(A\), denoted as \(A^{-1}\). The inverse of a \(2 \times 2\) matrix \(\begin{bmatrix} a & b \\ c & d \end{bmatrix}\) is given by \(\frac{1}{ad-bc} \begin{bmatrix} d & -b \\ -c & a \end{bmatrix}\). Calculating the determinant \(ad - bc\): \[ (-1)(-10) - (-6)(-3) = 10 - 18 = -8 \] Thus, the inverse of \(A\) is: \[ A^{-1} = \frac{1}{-8} \begin{bmatrix} -10 & 6 \\ 3 & -1 \end{bmatrix} = \begin{bmatrix} \frac{10}{8} & -\frac{6}{8} \\ -\frac{3}{8} & \frac{1}{8} \end{bmatrix} = \begin{bmatrix} \frac{5}{4} & -\frac{3}{4} \\ -\frac{3}{8} & \frac{1}{8} \end{bmatrix} \] Now, multiplying both sides of \(AX = B\) by \(A^{-1}\): \[ X = A^{-1}B \] Calculating: \[ X = \begin{bmatrix} \frac{5}{4} & -\frac{3}{4} \\ -\frac{3}{8} & \frac{1}{8} \end{bmatrix} \begin{bmatrix} 8 \\ 6 \end{bmatrix} = \begin{bmatrix} \frac{5}{4} \cdot 8 - \frac{3}{4} \cdot 6 \\ -\frac{3}{8} \cdot 8 + \frac{1}{8} \cdot 6 \end{bmatrix} \] Calculating the first entry: \[ \frac{5}{4} \cdot 8 - \frac{3}{4} \cdot 6 = 10 - 4.5 = 5.5 \] Calculating the second entry: \[ -\frac{3}{8} \cdot 8 + \frac{1}{8} \cdot 6 = -3 + \frac{3}{4} = -2.25 \] Thus, the solution to the system of equations is: \[ X = \begin{bmatrix} 5.5 \\ -2.25 \end{bmatrix} \] And the inverse matrix used is \[ A^{-1} = \begin{bmatrix} \frac{5}{4} & -\frac{3}{4} \\ -\frac{3}{8} & \frac{1}{8} \end{bmatrix}. \]